2018
DOI: 10.1038/s41598-018-26228-4
|View full text |Cite
|
Sign up to set email alerts
|

Selective improvements in balancing associated with offline periods of spaced training

Abstract: Benefits from post-training memory processing have been observed in learning many procedural skills. Here, we show that appropriate offline periods produce a performance gain during learning to stand on a multiaxial balance board. The tilt angle and the area of sway motion of the board were much more reduced in participants performing a training spaced by an interval of one day with respect to participants executing the same amount of practice over a concentrated period. In particular, offline memory encoding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 53 publications
1
7
0
Order By: Relevance
“…The possibility that a saturated level of performance triggers the benefits from spaced practice was suggested by Hauptmann et al [11] in regard to the repetition priming effects. Our results on a throwing task combined with previous findings on balancing [14] and visuomotor rotation [15] extend this scheme to the motor domain and suggest that the number of repetitions to achieve a stable performance may depend on the type of task. For tasks requiring a relatively low number of sensory and motor components-such as finger tapping or reaction time skills-the performance may stabilize during the first training session.…”
Section: Amount Of Practice and Offline Gainsupporting
confidence: 82%
See 1 more Smart Citation
“…The possibility that a saturated level of performance triggers the benefits from spaced practice was suggested by Hauptmann et al [11] in regard to the repetition priming effects. Our results on a throwing task combined with previous findings on balancing [14] and visuomotor rotation [15] extend this scheme to the motor domain and suggest that the number of repetitions to achieve a stable performance may depend on the type of task. For tasks requiring a relatively low number of sensory and motor components-such as finger tapping or reaction time skills-the performance may stabilize during the first training session.…”
Section: Amount Of Practice and Offline Gainsupporting
confidence: 82%
“…In our previous paper on learning precision throwing [12], we demonstrated that the complexity associated with the ball release parameters was optimized after a first accuracy stabilization. Similarly, when studying the spaced learning during balancing [14], some parameters associated with the structure of the movement strategy showed a delay in the offline gain. Moreover, the association between offline gain and movement optimization may also be supported by the parallel changes observed between the R E and the error along the two directional components.…”
Section: Amount Of Practice and Offline Gainmentioning
confidence: 97%
“…According to the underlying cellular and molecular mechanisms relating to spaced learning, the time interval between 2 stimuli should be at least 1 daydto achieve synaptic formation and strengthening. Additionally, Casabona et al 27 investigated the learning involved when mastering how to stand on a multiaxial balance board and suggested that an interval of 1 day was appropriate to activate the required level of offline memory consolidation in motor skill learning and improve performance. Therefore, in our retraining schedule, participants retrained on the same tasks with a 1-day interval between tasks.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that predictive control is a specific and critical factor for the successful transition from linear to curved walking, we suggest reinforcing those rehabilitative protocols addressed to stimulating the sensory feedback from the residual limb segments so as to trigger an update of the internal body representation and the forward models. For example, considering that amputees have no neurological injury, using the appropriate accommodations, the use of a tool such as a balance board can be important to stimulate the proprioceptive afferences and produce learning of new postural skills, as was demonstrated for healthy individuals [ 43 , 44 ]. Moreover, recent studies have demonstrated that the use of new tools, such as motor imagery [ 19 , 45 ] and virtual reality [ 46 ], can provide an important support in training and monitoring the development and updating of internal models, in subjects with a lower limb amputation.…”
Section: Conclusion and Practical Implicationsmentioning
confidence: 99%